2020
DOI: 10.47276/lr.91.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Peek Acuity vs Snellen Chart for visual impairment screening in leprosy: a cross-sectional study

Abstract: Objective: Leprosy is a chronic infectious disease caused by Mycobacterium leprae, which has a high incidence of ocular involvement. Due to the need for good vision for leprosy patients, visual acuity becomes an essential early screening examination. The Snellen Chart has been commonly employed as the standard for measuring visual acuity. Nevertheless, it is immobile and time-consuming. A smartphone-based application, Portable Eye Examination Kit (Peek Acuity), is already known to be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As for Peek Acuity, various statistical findings between their app and the Snellen chart were observed. As such, Bastawrous et al in 2015 reported a Pearson correlation coefficient of 0.95, Irawati et al in 2020 reported a Cohen’s kappa value of 0.65, and Bhaskaran et al in 2022 reported an intraclass correlation coefficient (ICC) of 0.98 [ 3 , 12 , 33 ]. Meanwhile, other apps such as Eye Chart reported an ICC between 0.74 and 0.88, Eye Chart Pro reported an ICC of 0.99, and Vision at Home as a tolerant quadratic weighted a kappa between 0.74 and 0.95 [ 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for Peek Acuity, various statistical findings between their app and the Snellen chart were observed. As such, Bastawrous et al in 2015 reported a Pearson correlation coefficient of 0.95, Irawati et al in 2020 reported a Cohen’s kappa value of 0.65, and Bhaskaran et al in 2022 reported an intraclass correlation coefficient (ICC) of 0.98 [ 3 , 12 , 33 ]. Meanwhile, other apps such as Eye Chart reported an ICC between 0.74 and 0.88, Eye Chart Pro reported an ICC of 0.99, and Vision at Home as a tolerant quadratic weighted a kappa between 0.74 and 0.95 [ 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%